The Learning and Educational Capital of Male and Female Students in STEM Magnet Schools and in Extracurricular STEM Programs: A Study in High-Achiever-Track Secondary Schools in Germany. (December 2017) - Stoeger, Heidrun; Greindl, Teresa; Kuhlmann, Johanna; Balestrini, Daniel Patrick
Magnet schools focused on science, technology, engineering, and mathematics (STEM) as well as extracurricular programs in STEM support talented students and help increase their participation rates in those domains. We examined whether and the extent to which the learning and educational capital of male and female students ( N = 801) enrolled in high-achiever-track secondary schools in Germany with and without a STEM focus differed. We found both school and gender differences for some types of learning and educational capital but no interaction effect of type of school and gender. We also assessed the relationship between school status as a STEM magnet school, students' gender, and students' learning and educational capital, on the one hand, and registration for a 1-year extracurricular program in STEM, on the other hand. Students enrolled in high-achiever-track STEM magnet schools, as well as male students, were more likely to register for the extracurricular program. Some types of learning and educational capital also predicted registration in a regression analysis.